Therapeutic Potential of Punica granatum and Isolated Compounds: Evidence-Based Advances to Treat Bacterial Infections - Mendes, Priscila Mendonça; Gomes Fontoura, Guilherme Martins; Rodrigues, Liliane dos Santos; Souza, Aloiso Sampaio; Viana, Jesse Pereira Machado; Fernandes Pereira, Ana Lucia; Dutra, Richard Pereira; Nogueira Ferreira, Adriana Gomes; Neto, Marcelino Santos; Reis, Aramys Silva; Berretta, Andresa Aparecida; Monteiro-Neto, Valério; et al. (International Journal of Microbiology, 2023)
Punica granatum Linn has been known for its nutritional and medicinal value since ancient times and is used in the treatment of various pathologies owing to its antibacterial properties. This review reports the results of the most recent studies on the antibacterial effects of P. granatum and its isolated compounds on bacteria of clinical interest. A search in the PubMed, Scopus, Science Direct, and Science Citation Index Expanded (Web of Science) databases was performed, which included articles that evaluated the antibacterial activity of P. granatum extracts and excluded articles that analyzed other microorganisms or nonpathogenic bacteria, as well as theses, dissertations, duplicate articles, and those not fully available. The literature suggests that P. granatum extracts can act on bacteria, such as methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant S. aureus (MRSA), Streptococcus mutans, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. In addition, fruit peel was the most commonly used pharmacogen and methanol, ethanol, and water were the most common solvents for the extraction of bioactive compounds. The antibacterial potential of the methanolic extract of pomegranate peel could be attributed to the presence of active compounds, such as 5-hydroxymethylfurfural, punicic acid, gallic acid, and punicalagin. Thus, there is evidence that these plant extracts, having high polyphenol content, can disrupt the bacterial plasma membrane and inhibit the action of proteins related to antimicrobial resistance. P. granatum shows antibacterial activity against Gram-positive and Gram-negative bacteria, with great potential against multidrug-resistant strains. Further research is needed to clarify the mechanism of action related to this biological activity and investigate the isolated substances that may be responsible for the antibacterial effects.